The Challenge to Change Reforming Health Care on the Front Line in the United States and the United Kingdom - Givan, Rebecca Kolins (Cornell University Press, 2016)
There is constant pressure on hospitals to improve health care delivery and increase cost effectiveness. New initiatives are the order of the day in the dramatically different health care systems of the United States and Great Britain. Often, as we know all too well, these efforts are not successful. In The Challenge to Change, Rebecca Kolins Givan analyzes the successes and failures of efforts to improve hospitals and explains what factors make it likely that the implementation of reforms will rewarded by positive transformation in a particular institution's day-to-day operation. Givan's in-depth qualitative case studies of both top-down initiatives and changes first suggested by staff on the front lines of care point clearly to the importance of all hospital workers in effecting change and even influencing national policy.Givan illuminates the critical role of workers, managers, and unions in enabling or constraining changes in policies and procedures and ensuring their implementation. Givan spotlights an Anglo-American model of hospital care and work organization, even while these countries retain their differences in access and payment. Entrenched professional roles, hierarchical workplace organization, and the sometimes-detached view of policymakers all shape the prospects for change in hospitals. Givan provides important examples of how the dedication and imagination of the people who work in hospitals can make all the difference when it comes to providing quality health care even in a challenging economic environment.There is constant pressure on hospitals to improve health care delivery and increase cost effectiveness. New initiatives are the order of the day in the dramatically different health care systems of the United States and Great Britain. Often, as we know all too well, these efforts are not successful. In The Challenge to Change, Rebecca Kolins Givan analyzes the successes and failures of efforts to improve hospitals and explains what factors make it likely that the implementation of reforms will be rewarded by positive transformation in a particular institution's day-to-day operation. Givan's in-depth qualitative case studies of both top-down initiatives and changes first suggested by staff on the front lines of care point clearly to the importance of all hospital workers in effecting change and even influencing national policy.Givan illuminates the critical role of workers, managers, and unions in enabling or constraining changes in policies and procedures and ensuring their implementation. Givan spotlights an Anglo-American model of hospital care and work organization, even while these countries retain their differences in access and payment. Entrenched professional roles, hierarchical workplace organization, and the sometimes-detached view of policymakers all shape the prospects for change in hospitals. Givan provides important examples of how the dedication and imagination of the people who work in hospitals can make all the difference when it comes to providing quality health care even in a challenging economic environment.